Hip Arthroscopy for the Treatment of Femoroacetabular Impingement Syndrome in Hips With Mild Osteoarthritis (Tönnis Grade 1): A Matched Comparative Cohort Analysis at Minimum 5-Year Follow-up. Issue 10 (August 2022) - Sivasundaram, Lakshmanan; Rice, Morgan W.; Horner, Nolan S.; Alter, Thomas D.; Ephron, Christopher G.; Nho, Shane J.
Background: There is a paucity of information in the literature on midterm outcomes from the arthroscopic treatment of femoroacetabular impingement syndrome (FAIS) with concomitant labral treatment in patients with mild osteoarthritis (OA) using modern surgical techniques. Purpose: To compare outcomes of hip arthroscopy for the treatment of FAIS between patients with mild OA (Tönnis grade 1) and patients without OA (Tönnis grade 0) at minimum 5-year follow-up. Study Design: Cohort study; Level of evidence, 3. Methods: Patients were identified who underwent primary hip arthroscopy for FAIS with routine capsular closure between January 2012 and December 2015. Patients with Tönnis grade 1 were matched 1:3 by age, sex, and body mass index to patients without OA. The Hip Outcome Score–Activities of Daily Living (HOS-ADL), HOS–Sports Subscale (HOS-SS), modified Harris Hip Score, and 12-item International Hip Outcome Tool were collected preoperatively and at 5 years postoperatively and compared between groups using an independent t test. Survivorship rate and percentage achievement of a Patient Acceptable Symptom State (PASS) or minimal clinically important difference (MCID) were compared using a Fisher exact test. Results: A total of 50 patients (54 hips) with Tönnis grade 1 were matched to 162 patients (162 hips) with Tönnis grade 0. The mean ± SD age and body mass index of the Tönnis grade 1 group were 44.5 ± 9.6 years and 28.5 ± 5.5, respectively. Patient-reported outcome (PRO) scores improved significantly for both groups from presurgery to 5 years postoperatively for all PROs ( P ≤ .03). There were no significant differences in preoperative PROs between the groups. Patients with Tönnis grade 1 had significantly lower postoperative scores on the HOS-ADL (74.7 ± 22.6 vs 83.0 ± 20.1; P = .04) and HOS-SS (58.8 ± 33.7 vs 71.8 ± 29.3; P = .03) than patients with grade 0. Patients with Tönnis grade 1 also had significantly lower rates of achievement of the MCID (57.1% vs 80.2%; P < .01) and PASS (34.1% vs 53.4%; P = .03) for any PRO when compared with patients with Tönnis grade 0. Gross survivorship was significantly lower for Tönnis grade 1 versus grade 0 (77.8% vs 96.9%; P < .001). Conclusion: Patients with Tönnis grade 1 arthritis experienced significant improvement in PROs after hip arthroscopy for the treatment of FAIS. However, they had significantly lower postoperative HOS-ADL and HOS-SS scores with significantly lower rates of achievement on the MCID and PASS, with a significantly lower gross survivorship rate at a minimum 5 years postoperatively in comparison with those with Tönnis grade 0 changes.